Social networks, role models, peer effects, and aspirations - Anandi Mani; Emma Riley (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
We review the literature on pathways through which social networks may influence social mobility in developing countries. We find that social networks support members in tangible ways-via access to opportunities for migration, credit, trading relationships, information on jobs, and new technologies-as well as in intangible ways, such as shaping their beliefs, hopes, and aspirations, through role models and peers. Nevertheless, networks can disadvantage non-members, typically the poor and marginalized. Recent evidence suggests a range of policy tools that could help mitigate disadvantages faced by excluded groups: temporary incentives to encourage experimentation into new regions, occupations, or technologies, and role models-real and virtual-to mitigate psychosocial challenges faced by marginalized groups. Targeting large fractions of marginalized groups simultaneously could increase the effectiveness of such policies by leveraging the influence of existing social networks.
Keywords: D9; Z1; O15; R23; 330; Global; Global; Soziale Ausgrenzung; Social exclusion